The Search for a Plural America: Protestant and Enlightenment Authority in American History. (6th January 2016) - Finstuen, Andrew
Abstract : A crisis of authority defines modernity. The crisis in the Christian West dates to the Reformation and the church-and-state conflicts based upon the question: whose Christianity? The crisis deepened during the Enlightenment as advances in science, reason, and technology changed the question: Christianity or not? By the 1960s, post-structuralism or postmodernity had posed the very question of authority and asserted competing authorities.